User Behavior Based Friend Recommendation in Facebook Social Networks - Dhawan, Sanjeev; Singh, Kulvinder; Gupta, Honey (International Journal of Computer Sciences and Engineering, 2025)
Social Network provides different applications like Facebook, Twitter, Skype and Instagram through which different users can use them and share their thoughts, images, videos and feelings with their friends. It is very difficult for a user to recommend friends to other new users. In this paper a survey of existing friend recommendation techniques such as Match maker, content based and geographical based recommendation has been presented after that this paper provides mechanism how a friend will be recommended to new user in Facebook social network.